Doping Dependent Magnetic Behavior in MBE Grown GaAs(1-x)Sb(x) Nanowires - Kumar, Raj (Sci Rep, 2020)
Intrinsic and Te-doped GaAsSb nanowires with diameters ~100–120 nm were grown on a p-type Si(111) substrate by molecular beam epitaxy (MBE). Detailed magnetic, current/voltage and low-energy electron energy loss spectroscopy measurements were performed to investigate the effect of Te-doping. While intrinsic nanowires are diamagnetic over the temperature range 5–300 K, the Te-doped nanowires exhibit ferromagnetic behavior with the easy axis of magnetism perpendicular to the longitudinal axis of the nanowire. The temperature dependence of coercivity was analyzed and shown to be in agreement with a thermal activation model from 50–350 K but reveal more complex behavior in the low temperature regime. The EELS data show that Te doping introduced a high density of states (DOS) in the nanowire above the Fermi level in close proximity to the conduction band. The plausible origin of ferromagnetism in these Te-doped GaAsSb nanowires is discussed on the basis of d(0) ferromagnetism, spin ordering of the Te dopants and the surface-state-induced magnetic ordering.